Robust Boolean reasoning for equivalence checking and functional property verification. - Kuehlmann, A. (IEEE Transactions on computer-aided design of integrated circuits and systems)
Many tasks in computer-aided design (CAD), such as equivalence checking, property checking, logic synthesis, and false paths analysis, require efficient Boolean reasoning for problems derived from circuits. Traditionally, canonical representations, e.g., binary decision diagrams (BDDs), or structural satisfiability (SAT) methods, are used to solve different problem instances. Each of these techniques offer specific strengths that make them efficient for particular problem structures. However, neither structural techniques based on SAT, nor functional methods using BDDs offer an overall robust reasoning mechanism that works reliably for a broad set of applications. The authors present a combination of techniques for Boolean reasoning based on BDDs, structural transformations, an SAT procedure, and random simulation natively working on a shared graph representation of the problem. The described intertwined integration of the four techniques results in a powerful summation of their orthogonal strengths. The presented reasoning technique was mainly developed for formal equivalence checking and property verification but can equally be used in other CAD applications. The authors' experiments demonstrate the effectiveness of the approach for a broad set of applications.